TEACHERS’ PERCEPTIONS OF FACTORS AFFECTING THE USE OF HEARING ASSISTIVE DEVICES TO IMPROVE LEARNING OUTCOMES AMONG STUDENTS WITH HEARING IMPAIRMENTS IN INCLUSIVE CLASSROOMS - Supermaniam, Murugesu; Muniandy, Mageswary N (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This qualitative study investigates teachers' views on the implementation of Hearing Assistive Devices (HADs) to facilitate learning by hearing-impaired students in inclusive classes. Although their effectiveness in enhancing auditory access has been rigorously proven, their systematic use in schools, especially in special education, is low. The research has three aims: (1) to explore the views of teachers about the potential of HADs in the support of hearing-impaired students, (2) to identify facilitators and barriers that influence the use of HADs, and (3) to uncover methods by which teachers modify lesson plans to incorporate HADs successfully. Data were gathered through semi-structured interviews with three veteran special education teachers and analysed thematically according to Braun and Clarke's six-phase method. Analysis of the interviews yielded four prominent themes: (i) readiness and awareness of HADs among teachers, (ii) benefits of HADs towards promoting pupil motivation and understanding, (iii) emotional and social difficulties experienced by pupils using HADs, and (iv) significance of institutional support and instructional practices, e.g., modifications to conventional instruction practices. This research contributes to inclusive education literature by placing a focus on the interconnectedness of pedagogy, assistive technology, and students' outcomes. It leverages Bronfenbrenner's ecological systems theory and the Technology Acceptance Model (TAM) to present an integrative theoretical model for HAD implementation in classrooms. Results emphasize the need for targeted professional development, enhanced technical support, and family-based interventions to mitigate stigma and ensure sustained use of HAD. Results are pertinent to policymakers, teacher educators, and school leaders in developing appropriate strategies for enhancing the learning experiences of hearing-impaired pupils in inclusive classrooms.